True West : authenticity and the American West - Handley, William R.; Lewis, Nathaniel, 1962- (Lincoln : University of Nebraska Press, 2004)
In no other region of the United States has the notion of authenticity played such an important yet elusive role as it has in the West. Though pervasive in literature, popular culture, and history, assumptions about western authenticity have not received adequate critical attention. Given the ongoing economic and social transformations in this vast region, the persistent nostalgia and desire for the "real" authentic West suggest regional and national identities at odds with themselves. True West explores the concept of authenticity as it is used to invent, test, advertise, and read the West. The fifteen essays collected here apply contemporary critical and cultural theory to western literary history, Native American literature and identities, the visual West, and the imagining of place. Ranging geographically from the Canadian Prairies to Buena Park's Entertainment Corridor in Southern California, and chronologically from early tourist narratives to contemporary environmental writing, True West challenges many assumptions we make about western writing and opens the door to an important new chapter in western literary history and cultural criticism.
Part I. Rhetorics of Authenticity. Truth or consequences : projecting authenticity in the 1830s / Nathaniel Lewis -- Cowgirls and sage hens : Henry Adams's western fantasy / Lisa MacFarlane -- Getting the real story : implications of the demand for authenticity in writings from the Canadian West / Alison Calder -- Willa Cather : "The West authentic," the West Divided / William R. Handley -- Part II. Authenticity and Native American Cultures. Simulations of authenticity : imagined Indians and sacred landscape from New Age to nature writing / Drucilla Mims Wall -- "Real Indian art" : Charles Eastman's search for an authenticating culture concept Christine Edwards Allred -- The only real Indians are Western ones : authenticity, regionalism, and Chief Buffalo Child Long Lance, or Sylvester Long / Nancy Cook -- The authenticity game : "Getting Real" in contemporary American Indian literature / Susan Bernardin -- Part III. Picturing Histories. Edward Curtis : pictorialist and ethnographic adventurist / Gerald Vizenor -- Animal calling/calling animal : threshold space in Frederic Remington's Coming to the call / Stephen Tatum -- "Cameras and photographs were not permitted in the camps" : photographic documentation and distortion in Japanese American internment narratives / Melody Graulich -- Part IV. Reimagining Place. Authenticity, occupancy, and credibility : Rick Bass and the rhetoric of protecting place / Scott Slovic -- Authoring an authentic place : environmental and literary stewardship in Stegner and Kittredge / Bonney MacDonald -- "Genealogy is in our blood" : Terry Tempest Williams and the redemption of "Native" Mormonism / Joanna Brooks -- Authentic re-creations : ideology, practice, and regional history along Buena Park's entertainment corridor / Hsuan L. Hsu.
Includes bibliographical references and index.
Electronic reproduction.
Master and use copy. Digital master created according to Benchmark for Faithful Digital Reproductions of Monographs and Serials, Version 1. Digital Library Federation, December 2002.
digitized
Print version record.
English.
Keywords: American literature -- West (U.S.) -- History and criticism; West (U.S.) -- Historiography; West (U.S.) -- In literature; Realism in literature; Réalisme dans la littérature.; LITERARY CRITICISM -- American -- General; American literature; Historiography; Literature; Realism in literature; West United States; Authenticiteit; Geschiedschrijving; Regionale geschiedenis (wetenschap); Westen (Verenigde Staten); Criticism, interpretation, etc